2009
DOI: 10.1175/2008jas2792.1
|View full text |Cite
|
Sign up to set email alerts
|

A Continuum of Sudden Stratospheric Warmings

Abstract: The k-means cluster technique is used to examine 43 yr of daily winter Northern Hemisphere (NH) polar stratospheric data from the 40-yr ECMWF Re-Analysis (ERA-40). The results show that the NH winter stratosphere exists in two natural well-separated states. In total, 10% of the analyzed days exhibit a warm disturbed state that is typical of sudden stratospheric warming events. The remaining 90% of the days are in a state typical of a colder undisturbed vortex. These states are determined objectively, with no p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 16 publications
5
26
1
Order By: Relevance
“…Strangely, we find no major SSWs for even stronger forcing h 0 $ 6000 m; in such cases, the stratospheric state at 10 hPa exhibits a very high degree of interannual variability-in some winters the vortex never becomes strong-with violent midwinter disturbances that, however, fail to meet the major SSW criterion of a wind reversal at 608N. This fact may just be an indication of the arbitrariness of this criterion (Coughlin and Gray 2009), rather than having any more fundamental implications. FIG.…”
Section: June 2015 S H E S H a D R I E T A Lmentioning
confidence: 66%
“…Strangely, we find no major SSWs for even stronger forcing h 0 $ 6000 m; in such cases, the stratospheric state at 10 hPa exhibits a very high degree of interannual variability-in some winters the vortex never becomes strong-with violent midwinter disturbances that, however, fail to meet the major SSW criterion of a wind reversal at 608N. This fact may just be an indication of the arbitrariness of this criterion (Coughlin and Gray 2009), rather than having any more fundamental implications. FIG.…”
Section: June 2015 S H E S H a D R I E T A Lmentioning
confidence: 66%
“…However, in reality they are often very similar to major warming events. Coughlin and Gray (2009) used the k-means clustering technique as a method of distinguishing between disturbed and undisturbed vortex states. However, using the traditional diagnostics of zonal mean winds and temperatures they found that the stratosphere was naturally split into only two states using this technique (i.e., they could not further subdivide the disturbed vortex state into splits and displacements).…”
Section: Further Analysismentioning
confidence: 99%
“…During these extreme events the NH polar vortex has been shown to have a direct influence on tropospheric variability (e.g., Baldwin and Dunkerton 2001;Thompson et al 2002;Bell et al 2009). Furthermore, studies have shown that the winter stratosphere is in a highly disturbed state for around 10% of the time (e.g., Coughlin and Gray 2009). However, due to the lack of planetary waves in the SH, SSWs are almost nonexistent (e.g., Charlton et al 2004;Esler et al 2006) and most of the variability is observed in the upper stratosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al (2009) used a nonlinear neural network to receive an alternative representation of the QBO. Coughlin and Gray (2009) use the K-Means cluster algorithm to determine two distinct states in the polar stratosphere, one representing normal, the other weak vortex conditions. Nao et al (2006) presents a technique based on support vector machines to estimate the surface area of polar stratospheric clouds.…”
Section: Statistical Modelsmentioning
confidence: 99%